STRUCTURAL ANALYSIS OF THE COMPOSITION OF “BOBURNOMA” (Scientific journal of the Fergana State University, 2025)
In this article, each artistic work has its own compositional types according to the features of form and content, depending on the genre of this work, it can have different looks, in the structural analysis of the composition of the artistic work, the order of its internal construction along with a wider study, it is possible to observe how the logical meaning of the content corresponds to the artistic intention of the creator, and on this basis, the composition of the work "Baburnoma" by Zahiriddin Muhammad Babur is structurally analyzed.